The Effectiveness of Discovery Learning in Enhancing Senior High School Students’ Critical Thinking Skills on Heat and Temperature Topics - Azzahra Dwi Ryogi Djamil; Rudi Haryadi (IAIN Sorong, 2026)
Teachers in 21st-century learning are expected to adapt their teaching to match the demands of that kind of learning. Critical thinking skills are essential competencies in physics learning; however, many students still experience difficulties in anlyzing problems, evaluating information, and drawing conclusions, particularly in heat and temperature topics. Therefore, effective learning models are needed to improve students’ critical thinking skills. This study aimed to determine the effectiveness of the Discovery Learning model in improving students’ critical thinking skills on heat and temperature material. The study employed a quasi-experimental method using a non-equivalent control group design. The participants consisted of 31 students in the experimental class and 31 students in the control class. Data were collected through critical thinking tests and students response questionnaires and were analyzed using N-Gain and the Mann-Whitney U Test. The result revealed that the average n-gain score of the experimental class was 0,5647, while the control class obtained 0,3213, both categorized as moderate. The mann u test showed a significance value of less than 0,0001, indicating a significant difference between the two classes. In addition, student responses reached 82,5%, which was categorized as very good. These findings indicate that the Discovery Learning model is effective in improving students’ critical thinking skills and can be considered an alternative learning model for physics instruction, particularly in heat and temperatur topics.